Heat transfer characteristics of R‐454B and R‐454B/POE‐oil mixture on smooth and GEWA tube: Alternative to R‐410A - Kumar, Abhishek; Wang, Chi-Chuan (International journal of heat and mass transfer, 2022)
•Pool boiling heat transfer of blends R-454B and R-410A is reported.•Tests are conducted on smooth and GEWA-B5H tubes at different evaporator pressure.•Heat transfer coefficients of R-454 are 26 – 34% lower than R-410A on both tubes.•The effect of POE-oil (mass fraction: 0 – 10%) on HTCs with R-454B is investigated.•HTC of the R-454B/oil mixtures was appreciably affected by the evaporator pressure. To clarify the compatibility of low GWP refrigerant R-454B alternative to high GWP refrigerant R-410A, the pool boiling heat transfer characteristics is presented subject to lubricant oil POEA-68. The tests were conducted on a smooth and highly structured GEWA-B5H tube at different saturated temperatures of 10, 0, and, −6 °C in 10 to 90 kW/m2 heat flux range. Results show that on both tubes the average heat transfer coefficient (HTC) of pure R-454B at all the saturation temperatures and heat flux is 26 to 34% lower than the pure R-410A. The heat transfer capacity of the GEWA-B5H tube is 2.5 to 5.5 times higher than compared to the smooth copper tube at the same saturation temperature and heat flux for both refrigerant R-454B and R-410A. Yet to elucidate the compatibility of POE oil with R-454B, the low viscosity oil POEA-68 is added by a mass fraction (ω%) of 1% to 10% and 0.25% to 5% for the smooth and GEWA-B5H tube, respectively. The mixing of oil alters the HTC, augmentation or deterioration in HTC compared to pure refrigerant is dependent on the liquid pressure (evaporator pressure), heat flux, boiling surface, and mass fraction of oil.